3(a+2)=2(a-7)

Simple and best practice solution for 3(a+2)=2(a-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a+2)=2(a-7) equation:


Simplifying
3(a + 2) = 2(a + -7)

Reorder the terms:
3(2 + a) = 2(a + -7)
(2 * 3 + a * 3) = 2(a + -7)
(6 + 3a) = 2(a + -7)

Reorder the terms:
6 + 3a = 2(-7 + a)
6 + 3a = (-7 * 2 + a * 2)
6 + 3a = (-14 + 2a)

Solving
6 + 3a = -14 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
6 + 3a + -2a = -14 + 2a + -2a

Combine like terms: 3a + -2a = 1a
6 + 1a = -14 + 2a + -2a

Combine like terms: 2a + -2a = 0
6 + 1a = -14 + 0
6 + 1a = -14

Add '-6' to each side of the equation.
6 + -6 + 1a = -14 + -6

Combine like terms: 6 + -6 = 0
0 + 1a = -14 + -6
1a = -14 + -6

Combine like terms: -14 + -6 = -20
1a = -20

Divide each side by '1'.
a = -20

Simplifying
a = -20

See similar equations:

| 11(4x+11)=-2 | | -4(-3+x)=48 | | 4(x-5)=3x-8 | | 2(-4+a)=-24 | | 6x-7x=12 | | 8g+18=62 | | 2(3+k)=2 | | 8y+328=4y | | 3x+9=42 | | 3(-2-4)=2(5-2+1) | | 3c^2+25c+50=0 | | 11x-6=3x^2 | | 5=x+10 | | x^2-4x-21=fector | | x^4-4x^3-12x^2=0 | | 4/12= | | 5x+7.2=4x | | P^2+2p-8= | | 4x^2-24x+27=0 | | 5v^2+3=-8v | | w+16=-8 | | 3X+47=0 | | r^2+2rh-35h^2= | | 4x-5=7(x-5) | | 3x-4y=27 | | -19n=323 | | -(x+3)+2(x+7)= | | 3+5u=-27 | | 8s^2+4s= | | 8y-3=4y+15 | | 2x^2-14x+3=0 | | 14r=126 |

Equations solver categories